Detection of Mycobacterium Tuberculosis Multiple Strains in Sputum Samples from Patients with Pulmonary Tuberculosis in South Western Uganda using MIRU-VNTR - Micheni, Lisa Nkatha; Kassaza, Kennedy; Kinyi, Hellen; Ntulume, Ibrahim; Bazira, Joel (Research Square, 2021)
Infections with multiple strains of Mycobacterium tuberculosis are now widely recognized as a common occurrence. Identification of patients infected with multiple strains, provides both insight into the disease dynamics and the epidemiology of tuberculosis. Analysis of Mycobacterial Interspersed. Repetitive Unit-Variable-Number Tandem Repeats (MIRU-VNTR) has been shown to be highly sensitive in detecting multiple M. tuberculosis strains even in sputum. The goal of this study was to identify cases of multiple M. tuberculosis strain infections among patients with pulmonary tuberculosis in south western Uganda and factors associated with multiple strain infections. Seventy-eight sputum samples were analyzed using the standard 24 loci MIRUVNTR typing and an exact regression analysis performed using Stata version 14. Five (6.4%) of the 78 patients were infected with multiple strains of M. tuberculosis. All of the patients infected with multiple strains were the newly diagnosed cases while one third of them were co-infected with HIV. These findings point to a critical component of disease dynamics that is most likely being overlooked at the clinical level, emphasizing the need to further study the potential high risk of exposure to these categories of patients at the community level using a larger sample size.
Keywords: Mycobacterium; Tuberculosis; Sputum samples; Pulmonary tuberculosis